Levels and trends of metals in human populations living in the Arctic - Bryan Adlard; Eva C. Bonefeld-Jørgensen; Alexey A. Dudarev; Kristin Olafsdottir; Khaled Abass; Pierre Ayotte; Élyse Caron-Beaudoin; Mallory Drysdale; Joshua Garcia-Barrios; Irina Gyllenhammar; Brian Laird; Melanie Lemire; et al. (International Journal of Circumpolar Health)
The 2021 Arctic Monitoring Assessment Program (AMAP)’s Human Health Assessment report presents a summary of the presence of contaminants in human populations across the circumpolar Arctic and provides an update to the previous assessment released in 2015. The primary objective of this paper is to summarise some of these findings by describing the current levels of metals across the Arctic, including key regional and temporal trends based on available national data and literature, and highlight knowledge gaps. Many Arctic populations continue to have elevated levels of these contaminants, and the highest levels of mercury (Hg) were observed in populations from Greenland, Faroe Islands, and Nunavik (Canada). Still, concentrations of several metals are declining in Arctic populations in regions where time trends data exist, although the declines are not consistent across all regions. The 2021 AMAP human health assessment report and this paper provide an extensive summary of levels of metals and trace elements in adults, pregnant women, and children across the Arctic.